2017
DOI: 10.1186/s12995-017-0179-0
|View full text |Cite
|
Sign up to set email alerts
|

“It’s still a great adventure” – exploring offshore employees’ working conditions in a qualitative study

Abstract: BackgroundDespite the particular demands inherent to offshore work, little is known about the working conditions of employees in the German offshore wind industry. To date, neither offshore employees’ job demands and resources, nor their needs for improving the working conditions have been explored. Therefore, the aim of this study was to conduct a qualitative analysis to gain further insight into these topics.MethodsForty-two semi-structured telephone interviews with German offshore employees (n = 21) and off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 34 publications
4
28
0
1
Order By: Relevance
“…We found that seeking social support from partners and families was another coping strategy for the interviewees, helping them to deal with the absences from home. This corresponds with previous research demonstrating regular contact with people onshore to be vital for offshore wind workers’ well-being [ 8 ]. Because the workers spend considerable time away from home, their chances to receive support from partners and families are limited.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that seeking social support from partners and families was another coping strategy for the interviewees, helping them to deal with the absences from home. This corresponds with previous research demonstrating regular contact with people onshore to be vital for offshore wind workers’ well-being [ 8 ]. Because the workers spend considerable time away from home, their chances to receive support from partners and families are limited.…”
Section: Discussionsupporting
confidence: 90%
“…Because the workers spend considerable time away from home, their chances to receive support from partners and families are limited. Therefore, access to means of communication is particularly relevant for the workers, as previously identified [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although considerable research exists on the working conditions, physical and psychological demands, and health issues of offshore workers from the offshore oil and gas industry, 11 the physical strains experienced by employees in the offshore wind energy branch have thus far only been addressed in qualitative studies. 12 The offshore wind and offshore oil and gas sectors share many similarities, but there remain important differences between the two industries, such as the type of installations and the extensive area of wind farms requiring frequent transport during offshore deployments. There are also similarities with the work in the onshore wind sector—that is, work in heights, climbing, type of installation—but comparability of both sectors is again limited due to the location of the installations, which demands, for example, the use of special safety and survival equipment during work.…”
Section: Discussionmentioning
confidence: 99%
“…Die Offshoretätigkeit geht mit hohen Anforderungen an die physische und psychische Belastbarkeit der Beschäf-tigten einher [5]. Die Beschäftigten arbeiten in einer tendenziell lebensfeindlichen Arbeitsumgebung, in der sie mit branchenspezifischen physischen und psychischen Belastungsfaktoren konfrontiert sind [6][7][8][9][10]. Bislang gibt es jedoch kaum empirische Ergebnisse zu den Arbeitsbedingungen, der möglichen Beanspruchung und der Gesundheit der Beschäftigten in diesem vergleichsweise jungen Industriezweig.…”
Section: Entwicklung Deutscher Offshorewindparksunclassified